Product portfolio management and performance: Evidence from a survey of innovative Brazilian companies - Jugend, Daniel [UNESP]; da Silva, Sérgio Luis; Salgado, Manoel Henrique [UNESP]; Miguel, Paulo Augusto Cauchick (Elsevier, 2016)
Portfolio management is gaining increasing attention from researchers and practitioners involved in innovation and product development. In this context, this study aims to analyze the product portfolio management practices that innovative firms in a developing country adopt. This investigation also aims to establish the relationship between these practices and product portfolio performance. The study carries out a quantitative survey on a sample of 71 Brazilian firms, and the results demonstrate that practices associated with formalization, systematization, and clarification in product portfolio decision making significantly influence the fulfillment of performance objectives. In addition, some companies face difficulty in fulfilling the balance of portfolio products, and this difficulty possibly relates to the concentration of incremental innovation efforts in new product development.
Keywords: Innovation management; New product development; Performance objectives; Product portfolio management